The art of path-making - Garcia Ruiz, M. (IX Graduate Conference in Cultural Studies: Building Narrative, 2019)
Light festivals have grown in popularity in recent years, being able to find a program of this kind in practically all European cities. This type of event consists of the programmed implementation of works or objects, with artistic value, in the public or semi-public space, with the intention of entertaining a large number of visitors. The location of these pieces is decided a priori, and the organization structure designs a map or “path” strategically based on these points. Although start and end points are defined, in base of different indicators, visitors are free to carry out their own itinerary, creating urban navigation tactics that better suit to their own interests while this awakes conflicts and opportunities that affect to the local economic night fabric. In this paper, we review how the different actors participating in a festival of light contribute to the design of these itineraries under a decertonian perspective. We will present this through a case study: Lumina Light Festival, and in particular the editions held in the town of Cascais (2013-18).